2011
DOI: 10.1002/ejoc.201100120
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free SN2′ Decarboxylative Rearrangement of β‐Keto Esters

Abstract: Treatment of 2‐methoxycarbonyl‐ (or 3‐cyano‐)allyl acetoacetates with a tertiary amine or triphenylphosphane afforded α‐methylene γ‐substituted δ‐keto esters (or nitrile) in satisfactory yields. Various bases and nucleophiles were tested to elucidate the mechanism. The results of the study strongly suggest an intermolecular pathway involving a SN2′–decarboxylation–SN2′ cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…In situ IR (infrared) and 1 H NMR spectroscopy and product studies have shown that acetoacetate allyl esters with an electron-withdrawing group on the C=C bond of the allyl moiety undergo an intermolecular S N 2 -decarboxylation-S N 2 reaction when treated with a base such as Et 3 N or triphenylphosphane (Scheme 4). 33 Overall yields range from 57 to 78%. Alkyl lithiums react with 3,3-difluoro-1-propenes in an S N 2 reaction, giving alkyl monofluoroalkenes in good to high yields (generally 70-97%).…”
Section: R R′ O Oacmentioning
confidence: 99%
“…In situ IR (infrared) and 1 H NMR spectroscopy and product studies have shown that acetoacetate allyl esters with an electron-withdrawing group on the C=C bond of the allyl moiety undergo an intermolecular S N 2 -decarboxylation-S N 2 reaction when treated with a base such as Et 3 N or triphenylphosphane (Scheme 4). 33 Overall yields range from 57 to 78%. Alkyl lithiums react with 3,3-difluoro-1-propenes in an S N 2 reaction, giving alkyl monofluoroalkenes in good to high yields (generally 70-97%).…”
Section: R R′ O Oacmentioning
confidence: 99%
“…In general, the ketone electrophiles were readily prepared in one or two steps (see the Supporting Information). Aliphatic ketones were well tolerated ( 2a , 2b ; Table ). Acetophenone derivatives with varying electronic properties were also competent in the reaction ( 2c – 2e ) but gave lower yields due to a more challenging reductive amination step.…”
mentioning
confidence: 99%